Flavonoid Isolation And Toxicity Test Using The BSLT (Brine Shrimp Lethality TestI) Method From Parasite Flower Coffe Extract (Loranthus ferrugineus Roxb.) - Roza, Destria; Girsang, Sedianta (Universitas Negeri Medan, 2024)
This research aims to isolate compounds from extracts of coffee parasite flowers (Loranthus ferrugineus Roxb.) and determine their toxicity activity using the BSLT (Brine Shrimp Lethality Test) method. The results of the identification of secondary metabolite compounds show that the coffee parasite flower extract contains alkaloids, saponins, tannins and flavonoids. The results of the toxicity activity of the coffee parasite flower extract using the BSLT method show that the extract has high bioactivity and has an LC50 value of 93.4266 µg/mL. Meanwhile, isolation of flavonoid compounds from coffee parasite flower extract (Loranthus ferrugineus Roxb.) based on infrared spectroscopy (IR) analysis showed the presence of vibrations of the O-H, Ð¡-Ð, Ð¡-Ðž, C-C, and C-O groups which indicated the presence of flavonoid group compounds.